Felicia y Odicia - Blanco Palacios, Maria Eugenia; Pacheco, Alma.; Pacheco, Guadalupe (Monterrey, Nuevo Leon, Mexico : Ediciones Castillo, 2000)
Una nina feliz y optimista y una nina siempre enojada tienen que trabajar juntas en la escuela y deciden hacer una apuesta.
A very happy, optimistic girl and another girl who is always angry have to work together in school. They decide to make a bet.
Keywords: School children -- Juvenile fiction; Escolares -- Novela; Spanish language materials